Extensive review of cloud resource management techniques in industry 4.0: Issue and challenges. (21st February 2020) - Dewangan, Bhupesh Kumar; Agarwal, Amit; Choudhury, Tanupriya; Pasricha, Ashutosh; Chandra Satapathy, Suresh
Summary: Resource provisioning in the cloud is the most popular business model for any service provider due to profit that is based on how resources are distributed among users in Industry 4.0. Moreover, much research carried out to provide a better resource provisioning system to service providers; however, efficient resource provisioning may save the environments too. This study presents an extensive analysis of different resource provisioning systems based on concert parameters. More than 250 relative research articles have been considered for this study, out of these 125 articles has been processed for comparative analysis on the basis of different performance metrics. This study highlights the classifications of resource management techniques, objective functions, and open research challenges and issues while analyzing resource management techniques. It also provides the depth knowledge of uses of performance metrics utilization based on its classifications.